2022
DOI: 10.1029/2022jg006942
|View full text |Cite
|
Sign up to set email alerts
|

Abundant Fe(III) Oxide‐Bound Arsenic and Depleted Mn Oxides Facilitate Arsenic Enrichment in Groundwater From a Sand‐Gravel Confined Aquifer

Abstract: High arsenic (As) groundwater (>10 μg/L) has been increasingly observed throughout the world (Bundschuh

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 109 publications
4
13
0
Order By: Relevance
“…However, the sources and characteristics of DOM in shallow and deep groundwater were poorly understood. Under this direction, a continuation of the previously reported works in the area (Gao et al, 2022;Guo, Zhang, et al, 2014) was formed here. The main goal of our approach is to (a) identify sources and molecular compositions of shallow and deep groundwater DOM, (b) estimate a paradigm describing groundwater DOM processing pathways under reducing conditions, and (c) reveal linkages of sources and degradation state of DOM with groundwater As enrichment in the deep aquifer.…”
supporting
confidence: 83%
See 4 more Smart Citations
“…However, the sources and characteristics of DOM in shallow and deep groundwater were poorly understood. Under this direction, a continuation of the previously reported works in the area (Gao et al, 2022;Guo, Zhang, et al, 2014) was formed here. The main goal of our approach is to (a) identify sources and molecular compositions of shallow and deep groundwater DOM, (b) estimate a paradigm describing groundwater DOM processing pathways under reducing conditions, and (c) reveal linkages of sources and degradation state of DOM with groundwater As enrichment in the deep aquifer.…”
supporting
confidence: 83%
“…The release of sedimentary WSOM was likely related to Fe(III) oxide reduction (Mladenov et al., 2010), which occurred considerably more in the deep aquifer than in the shallow one (Gao et al., 2022). The contents of the extracted Fe(II) minerals in deep sediments (average 12.3 mmol/kg), possibly reflecting the extent of Fe(III) oxide reduction, were around two‐fold as high as those in shallow sediments (average 5.68 mmol/kg) (Gao et al., 2022). Previously reported works in the literature have revealed that WSOM in sediments were higher in BIX values (Huang et al., 2015) and labile OM abundances (Qiao et al., 2020) than groundwater DOM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations